Ancient Human Mitogenome of the Beagle Channel (Tierra del Fuego): An Argentine Collaborative Project - Arencibia, Valeria; Muñoz Hidalgo, Marianne Graziel; Crespo, Cristian Marcelo; Maldonado, Lucas Luciano; Lichtenstein, Gabriel; Kamenetzky, Laura; Vera, Pablo; Zangrando, Atilio Francisco Javier; Tessone, Augusto; Avena, Sergio Alejandro; Lia, Verónica; Puebla, Andrea; et al. (Latin American Antiquity)
The increasing use of massively parallel sequencing in the study of current and ancient human populationshas enabled new approaches to bioanthropological and archaeological issues; however, its application toarchaeological samples requires the use of technologies that are not easily accessible outside US andEuropean research centers. To obtain an ancient mitogenome in Argentina, several institutions collaboratedto apply massively parallel sequencing and bioinformatic methodologies on an enriched ancient DNA libraryof an individual from the Beagle Channel (dated 1504 ± 46 years BP), a region of particular interest for thisline of inquiry. Phylogenetic reconstruction showed a close relationship with a Yamana from Navarino Islandand an individual from Hoste Island (Chilean Antarctic Province): the three shared an ancestor who livedbetween 203 and 4,439 years ago. These three have mutations reported only for current and ancient individuals from the Beagle Channel, and their relationship with the rest of the D1g sub-haplogroups is unclear. Theresults obtained here are consistent with the reduction of mobility in the Fuegian archipelago around 4500years BP that has been proposed based on archaeological evidence. Fil: Arencibia, Valeria. Universidad Maimónides. Área de Investigaciones Biomédicas y Biotecnológicas. Centro de Estudios Biomédicos, Biotecnológicos, Ambientales y de Diagnóstico; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Muñoz Hidalgo, Marianne Graziel. Instituto Nacional de Tecnología Agropecuaria. Centro de Investigación en Ciencias Veterinarias y Agronómicas. Instituto de Agrobiotecnología y Biología Molecular. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Agrobiotecnología y Biología Molecular; Argentina Fil: Crespo, Cristian Marcelo. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, Recursos Naturales y Ambiente; Argentina. Consejo Nacional de ...